Thermal properties of engine oils through the integration of graphene nanoparticles : A greener approach for sustainable mechanical systems - Kadirgama, Ganesaan; Muhammad Adam lee, Abdullah; Devarajan, Ramasamy; Kadirgama, Kumaran; Samykano, Mahendran; Yusaf, Talal F. (EDP Sciences, 2024)
Tribology is a high demand mechanical system with friction and wear. Mechanical systems lose efficiency as a result. One answer for this issue is to utilize an oil that can limit contact and wear, bringing about improved effectiveness. The advancement of effective lubricating added substances for tribological properties improvement and improved thermal conductivity has gotten huge modern and scholarly consideration. By and large, nano-sized particles scattered in lubricants, referred to as nano-based lubricant, are utilized in mechanical structures to lessen heat and forces of frictions. Moreover, new guidelines will empower the utilization of greener lubrication advancements in oils. To resolve this issue, lubricants should satisfy guidelines while able to give exceptional oil characteristics. As another green material, this research will investigate the dissolving of Graphene nanoparticles in lubricants. The objective of this study is to perceive what Graphene added 10W40 motor oil means for the thermal properties and tribological characteristics. Graphene, which was added to 10W40 lubricant, was used to study the best design. Graphene nanoparticles were distributed in baseline engine oil in a two-step process. In the preparation of Graphene-based motor oil with a low volume mixture in the scope of 0.01% to 0.07% was used. Thermal conductivity and viscosity are estimated for all volume mixtures. Testing uncovered that Graphene added 10W40 motor oil were steady all through the review, with very little deposits in the following 30 days. The thermal conductivity of Graphene in SAE 40 motor oil expanded as the volume mixture is added.